Construction of a Doxycycline-Dependent Simian Immunodeficiency Virus Reveals a Nontranscriptional Function of Tat in Viral Replication - Das, Atze T. (American Society for Microbiology, 2007)
In the quest for an effective vaccine against human immunodeficiency virus (HIV), live attenuated virus vaccines have proven to be very effective in the experimental model system of simian immunodeficiency virus (SIV) in macaques. However, live attenuated HIV vaccines are considered unsafe for use in humans because the attenuated virus may accumulate genetic changes during persistence and evolve to a pathogenic variant. As an alternative approach, we earlier presented a conditionally live HIV-1 variant that replicates exclusively in the presence of doxycycline (DOX). Replication of this vaccine strain can be limited to the time that is needed to provide full protection through transient DOX administration. Since the effectiveness and safety of such a conditionally live AIDS vaccine should be tested in macaques, we constructed a similar DOX-dependent SIVmac239 variant in which the Tat-TAR (trans-acting responsive) transcription control mechanism was functionally replaced by the DOX-inducible Tet-On regulatory mechanism. Moreover, this virus can be used as a tool in SIV biology studies and vaccine research because both the level and duration of replication can be controlled by DOX administration. Unexpectedly, the new SIV variant required a wild-type Tat protein for replication, although gene expression was fully controlled by the incorporated Tet-On system. This result suggests that Tat has a second function in SIV replication in addition to its role in the activation of transcription.